2013
DOI: 10.3917/pope.1301.0037
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Debut in Rabat: New “Arrangements” between the Sexes

Abstract: Sexual debut is an essential aspect of the socialization process (Balandier, 1984;Courtois, 1998). It is a major component of social control, and the manner in which it occurs provides information about how each society constructs the social and gendered identities of its members, and reveals the different rules of behaviour imposed upon girls and boys (Bozon, 2008).Recent representative surveys indicate that in most societies, first sexual intercourse is occurring at an earlier age today, and is more dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Bakass & Ferrand [37] found that the majority of the men and women in their sample felt that women virginity would guarantee her future prospect of marriage. This belief seems to be largely common in Morocco.…”
Section: Attitudes Towards Premarital Sexuality In Moroccomentioning
confidence: 96%
See 1 more Smart Citation
“…Bakass & Ferrand [37] found that the majority of the men and women in their sample felt that women virginity would guarantee her future prospect of marriage. This belief seems to be largely common in Morocco.…”
Section: Attitudes Towards Premarital Sexuality In Moroccomentioning
confidence: 96%
“…Global cultural homogenisation is far from being materialised at least so far as interaction between opposite sexes are concerned. Bakass & Ferrand [37] p.37 argue "The social and religious order in Morocco is still based on such values as the honour and good name of the family wherein premarital female sexuality is proscribed and an intact hymen is irrefutable evidence of a successful family upbringing". This is evident from the following extracts;…”
Section: Consequences Of Being Caughtmentioning
confidence: 99%
“…nuptiality change also creates tensions within families, especially because young people in the Arab world still prefer to marry (young), but can do so only at more advanced ages (Bakass and Ferrand 2013). Since marriage is postponed, young men and women keep on living, for an extended period of time, with their parents and remain under their authority.…”
Section: Introductionmentioning
confidence: 99%
“…In Ahmed and Ishraq's case, his mother worried her son might be taken to jail. At the time, though, the since abrogated article of the penal code allowing a man to avoid prosecution by marrying the woman he had sexual relations with still applied (Bakass, Ferrand, andDepledge 2013, 46, Kreutzberger 2008, Fioole HAWWA (2020) 34-54 39). Unlike Rabia's boyfriend, Ahmed did want to marry his girlfriend, and they were already living together as spouses.…”
mentioning
confidence: 99%